Edukasi perlindungan anak di dunia pendidikan pada sekolah MAN 1 Langkat - Lubis, Junaidi; Dermawan, Haris; Dekar, Muhammad; Lubis, Muhammad Koginta (Penamas: Journal of Community Service, 2024)
Children are a gift from Allah SWT, the Almighty God; therefore, their protection must be ensured to be given a high place so that in the future, the priority for the protection of children must be even better so that no more children become victims of the bad treatment that occurs, especially in the education world. Providing education to children is the responsibility of all parties so that child protection continues to improve daily, both in the social environment and especially in the educational environment. Child protection education at Madrasah Aliyah Negeri School (MAN) 1 Langkat represents a genuine concern for fulfilling children's rights in education. The Battuta University Law Study Program community service team collaborates with MAN 1 Langkat to carry out legal education activities regarding child protection in education. The methods used in this service are socialization and mentoring. The results of the service activities show that the students at MAN 1 Langkat school are thrilled; this can be seen from how seriously they listen to what is said and actively ask questions about children, children's rights, and how to implement protection in the school environment so that in the future they will understand their rights. Children in the world of education must be educated.